In our class, we described the voltage and the current across/in a transmission line as the sum/difference of progressing wave and regressing wave:

I(z,t) = I+(z,t) - I-(z,t)

V(z,t) = V+(z,t) + V-(z,t)

And that:

I+(z,t) = V+(z,t) / Zo

I-(z,t) = V-(z,t) / Zo

(Zo is the characteristic impedance of the transmission line).

In the bellow picture, I calculated I(z,t) and V(z,t) for t->∞.

V(z,t->∞) turned out to be equal V-(z,t->∞) = Vg (a regressing wave) which makes sense since in the steady state (t->∞), there is no voltage drop across the line.

But it turns out that (according to the above formulas):

I(z,t->∞) = -Vg /Zo.

How come there's current through the line, in steady state (t->∞) ?

Thanks.

I(z,t) = I+(z,t) - I-(z,t)

V(z,t) = V+(z,t) + V-(z,t)

And that:

I+(z,t) = V+(z,t) / Zo

I-(z,t) = V-(z,t) / Zo

(Zo is the characteristic impedance of the transmission line).

In the bellow picture, I calculated I(z,t) and V(z,t) for t->∞.

V(z,t->∞) turned out to be equal V-(z,t->∞) = Vg (a regressing wave) which makes sense since in the steady state (t->∞), there is no voltage drop across the line.

But it turns out that (according to the above formulas):

I(z,t->∞) = -Vg /Zo.

How come there's current through the line, in steady state (t->∞) ?

Thanks.

#### Attachments

Last edited: